Bibliometric Analysis on Precision Agriculture Technology - Loso Judijanto; Tera Lesmana (Westscience Press, 2024)
This study employs a bibliometric analysis using VOSviewer to visualize the authorship network within the domain of precision agriculture, identifying key researchers and their collaborative relationships. By mapping the connections based on publications from a specified time period, the analysis highlights the central figures like Erickson, B, who play pivotal roles in the network and reveals the interlinkages among various contributors. The study provides insights into the structural dynamics of research collaborations and elucidates the influence patterns among the scholars. Despite the inherent limitations such as database selection bias and the static nature of the bibliometric snapshot, the results offer valuable implications for enhancing research collaboration, academic planning, and strategic positioning within the scholarly community. This approach not only aids in recognizing influential entities and emerging talents but also assists institutions and funders in making informed decisions that could drive impactful research in precision agriculture.